Implementasi Terapi Reminiscence dalam Upaya Meningkatkan Harga Diri Lansia Penderita Penyakit Tidak Menular - Madepan Mulia; Heni Apriyani (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Non-communicable diseases (NCDs) such as diabetes mellitus, hypertension, and stroke are common health problems among the elderly. NCDs in the elderly affect not only physical conditions but also psychological ones, including decreased self-esteem. Elderly people with NCDs typically experience activity limitations, dependency on medication, and changes in social roles that can lead to feelings of helplessness and low self-esteem. This community service activity aims to implement reminiscence therapy as an effort to improve the self-esteem of elderly people with NCDs in Sukaraja Village. The implementation method is training/implementation of reminiscence therapy. The results of the activity showed an increase in the self-esteem score of elderly people with NCDs by 4.63. Thus, the implementation of reminiscence therapy in community service activities has proven to be an effective and applicable strategy in improving the self-esteem of elderly people with NCDs in the community.